Adrian Ivakhiv. Shadowing the Anthropocene: Eco-Realism for Turbulent Times - Faber, Roland (Journal for the study of religion, nature and culture, 2023)
Adrian Ivakhiv. Shadowing the Anthropocene: Eco-Realism for Turbulent Times(Santa Barbara: punctum books, 2018), 294 pp., $25 (pbk), ISBN: 9781947447875.